Active Suspension Based on a Motor-Driving Compacted Double-Gas-Chamber Hydro-Pneumatic Strut - Ruihong Li; Bing Ma; Fan Yang; Dezhao Lin; Weiqiang Zhang (IEEE Access)
Vehicle attitude is one of the most important factors affecting ride comfort, safety, and handling, and it is influenced by road conditions, driver’s maneuvers, and other factors. It is usually achieved by pumping methods (air suspension, hydro-pneumatic suspension, and so on). However, the nonlinearities, hysteresis, and uncertainties in the adjusting process caused by the gas property and the valve characteristic will increase the difficulty of controller design. And frequent use of the pump for continuous adjustment also affects the life span. This paper develops an active suspension based on Motor-driving compacted Double-gas-chamber Hydro-Pneumatic Strut (MDHPS) and verifies the possibility of attitude control with a simple PID controller. The controller is built based on the quarter-car model with the MDHPS model and the optimal values are identified through the Ziegler-Nichols method and Genetic Algorithm (GA). Finally, to investigate the attitude control effect of MDHPS, the full-car model is established based on the co-simulation of Carsim and Matlab/Simulink. The anti-roll and anti-pitch properties based on the proposed height adjustment method are evaluated under different working conditions. Through the comparison between the active and passive methods, it has been shown that the proposed method can greatly improves vehicle performance. The improvement rate of the Root Mean Square (RMS) for both roll and pitch angles exceeds 50.46% under different working conditions.